Pengaruh Kepuasan Kerja, Kompetensi, Komitmen Organisasional terhadap Kinerja Karyawan dengan Kepemimpinan Sebagai Variabel Moderator - Prayogi, Achmad Brian Fajar; Hamada, Abubakar; Asmoro, Aprianto Sandi; Firdaus, Vera (Universitas Proklamasi 45, 2025)
This study aims to investigate the impact of job satisfaction, competence, and organizational commitment on employee performance, while also evaluating the role of leadership as a moderating variable. A quantitative method, employing a survey approach, was used to collect data from 150 employees at a private company. The analysis results showed that organizational commitment and leadership had a positive and significant effect on employee performance, while job satisfaction and competence did not show a significant impact. However, simultaneously, all four variables had a significant effect on performance. This study highlights the importance of commitment and leadership in supporting employee performance, which positively impacts the achievement of organizational goals. These findings provide valuable insights for human resource management, particularly in employee planning and development to enhance the company's competitiveness.